Examining differences in time to appointment and no-show rates between rural telehealth users and non-users - Pullyblank, Kristin; Krupa, Nicole; Scribani, Melissa; Chapman, Amanda; Kern, Megan; Brunner, Wendy (Frontiers in Digital Health, 2024)
Background: Telehealth has undergone widespread implementation since 2020 and is considered an invaluable tool to improve access to healthcare, particularly in rural areas.However, telehealth's applicability may be limited for certain populations including those who live in rural, medically underserved communities. While broadband access is a recognized barrier, other important factors including age and education influence a person's ability or preference to engage with telehealth via video telehealth or a patient portal. It remains unclear the degree to which these digital technologies lead to disparities in access to care.Purpose: The purpose of this analysis is to determine if access to healthcare differs for telehealth users compared with non-users.Methods: Using electronic health record data, we evaluated differences in "time to appointment" and "no-show rates" between telehealth users and non-users within an integrated healthcare network between August 2021 and January 2022. We limited analysis to patient visits in endocrinology or outpatient behavioral health departments. We analyzed new patients and established patients separately.Results: Telehealth visits were associated with shorter time to appointment for new and established patients in endocrinology and established patients in behavioral health, as well as with lower no-show rates for established patients in both departments.Conclusions: The findings suggest that those who are unwilling or unable to engage with telehealth may have more difficulty accessing timely care.